Rebisco - Ayuco, Nieline Ianne I.; Perez, Cleo Rose F.; Ramos, Jonjielynn P.; Rebollido, Monique H. and Recondo, Jillian Rose E., 2017 4 0 16; 5
Abstract: Republic Biscuit Corporation (Rebisco) is part of the food industry classified as manufacturing. Manufacturing industry refers to those industries which involved in the manufacturing and processing of items and indulge in either creation of new commodities or in value addition. Rebisco now carries a wide variety of snack after 50 years of manufacturing products that generations of Filipinos have loved. Republic Biscuit Corporation (Rebisco) Is one of the leading bakery products manufacturer who put up several companies to dominate other segments of the market such as Suncrest Foods Incorporated , SPI Corporation, Multirich Food Corporation, Pinnacle Foods Incorporated and JBC Food Corporation. On the total income of the food industry, it covers almost a quarter of the overall sales of different industries. This means that the food industry is important to circulate in the market as it provides one of the basic needs of the target market. Rebisco on the other hand reached 41% of income to the other food industries. This signifies that the products offered by Rebisco are patronized by the consumers. Also, this means that the production of biscuits and crackers is in demand for the company manufacturing the goods has reached an income almost half of all the income of food industries in the country. The strengths of Rebisco are the consumers brand loyalty, innovative packaging, market leader and innovative product range. This makes them lasts in the industry and continuing as a leading company. However, its weaknesses such as online presence and weak brands are things that make them focused.With Rebisco as one of the leading company for dry baked goods, they innovate products that satisfy their consumers. We cant's just create answering the delight to taste of the consumers but every process done must undergo various researches and knowledge to provide the best goods for their consumers. Market research is done in making innovations and development on Rebisco products because they want to provide the consumers the goods that will not only satisfy them but will also give positive benefits to the. The researchers also conducted a survey to 150 people to collect information for the researchers to be more knowledgeable about Republic Biscuits Corporation (Rebisco) products and to know what points they have to focus on creating strategies that will help the company. The result of his survey is the basis the researchers follow in creating different strategies in helping the company to grow more. Part of strategy is launching a new product and creating a new packaging for the consumers. Also, there are promotions made to entice new consumers and the strategy on pricing is further explained. Also, there are list of best scenarios in case of the strategies implementation success and contingency plans for another strategies in case of failure because Rebisco is a leading company in the food industry and that we wanted that products of this company must be better than its competitors undergone various researches and discussions from the management.
Strategic Marketing Plan: (BSBA major in Marketing Management) - Pamantasan ng Lungsod ng Maynila, 2017.
Keywords: 2 -- 0; 6; 20; 20; 2